MODELING OF NEONATAL MORTALITY RATES IN NIGERIA: AN INSIGHT TO THE UNITED NATIONS SUSTAINABLE DEVELOPMENT GOAL (British Journal of Global Ecology and Sustainable Development, 2023)
• The third Sustainable Development Goal (SDG) explicitly states that it is a priority to reduce neonatal mortality rate to 12 deaths per 1,000 live births due to its importance to population dynamics. Comparing Nigeria to other Sub-Saharan African countries, the neonatal mortality rate remains unacceptably high. Nigeria has the highest rate of neonatal deaths in all of Africa. The objective of this research is to model and generate projections of NMR in Nigeria using a time series approach in order to ascertain if Nigeria will achieve the SDG target of NMR by 2030. Using data from UN-IGME 2022, STATA version 12 was used for this study's data analysis. According to the forecasts, Nigeria's Neonatal Mortality Rate (NMR) would drop to about 27 deaths per 1,000 live births by 2030. Even while this would represent a significant improvement over earlier rates, the overall NMR aim would still be greatly missed. The Annual Reduction Rate (ARR) of NMR in Nigeria would need to be significantly raised in order to reach the stated reduction in NMR mentioned in the Sustainable Development Goal of the United Nations by the year 2030.